Establishment and development of the Traditional Chinese Medicine nursing clinic based on theory of preventive treatment of diseases (某医院“治未病”中医护理门诊的建设与发展现状) - HAO Guangying (郝广英); LIU Xin (刘欣) (中西医结合护理)
This paper summarized the establishment and development status of the Traditional Chinese Medicine (TCM) nursing clinic based on theory of preventive treatment of disease. According to the outcomes of survey health needs of patients who visited the TCM nursing clinic, a working group was set up and related TCM characterized nursing services were established. Studding and training programs were systematically organized for nurses who met criteria. The continuous quality improvement management was adopted to address the problems of running and optimize the diagnosis and treatment process, and related appraisal mechanism was established. (本文介绍了某中医医院“治未病”中医护理门诊的建设和发展现状。通过前期调查“治未病”中医护理门诊需求, 制定中医特色专科护理服务内容, 成立中医护理门诊工作小组。确定中医护理门诊人员资质, 有计划进行学习、参观、培训。按计划开设中医护理门诊, 优化诊疗流程, 制定中医护理门诊考核机制, 对运行中存在的问题进行持续质量改进。)